#TITLE_ALTERNATIVE# - HANIFAH (NIM : 20514022) , SARINA
Lead is a metal which is widely used as a battery rare ingredient, pigments additives, metal coatings, wire coatings, material for bullets and fuel additives. Although it has a lot of benefits, lead metal waste can adversely affect human health. Lead exposure in humans can cause a variety of negative effects on health, for example in the central nervous and peripheral nerves, hypertension, renal, gastrointestinal, reproductive system, and it has carcinogenic effect. Based on data from the Ministry of Health of the Republic of Indonesia, the maximum standard levels of lead (Pb) in drinking water by Permenkes No. 492/Menkes/Per/IV/2010 amounted to 0,01 mg/L or 0,01 ppm. Several methods have been used in the processing of polluted water treatment such as chemical precipitation, membrane filtration, ion exchangers, liquid extraction and electrodialysis. These methods are less effective to use because it requires high operating costs and less suitable for water treatment in small scale. Adsorption method has been known as an effective process for reducing the metal ions from wastewater because it is easy to separate, and have a high effectiveness. The use of coffee biomass as adsorbent in powder form is less effective because it is difficult to separate after the adsorption process and has risk of mass lost during separation. Therefore, coffee biomas encapsulated in Ca-alginate can also increase the adsorption capacity because of carboxyl abundance in alginate. Two adsorbent used in this study are Ca-alginate (CA) and Ca-alginate-coffee (CAK). The research method was conducted using column and batch studies. The optimum adsorption conditions reached at pH 4, 2 hours and 0,05 gram of adsorbent. The maximum adsorption capacity (qm) is equal to 163,66 mg/g and 176,99 mg/g for CA and CAK. Both types of adsorbents followed the Langmuir isotherm and pseudo second order kinetic model. In the adsorption of a binary system, two types of adsorbent did not show ion selectivity toward Pb (II). Adsorption of binary systems showed that the % removal of Pb (II)> Cu (II)> Cd (II) for the adsorbent CA and CAK. The minimum time to adsorb Pb (II) ions on the column study is 3.5 hours. Desorption of Pb (II) with HNO3 showed a reduction in the percentage of each cycle which is equal to 101.2; 96.35 and 86.64%.